Parametric Study of Mixed Convective Radiative Heat Transfer in an Inclined Annulus - Al-Hafidh, Manal H. (Al-Khwarizmi Engineering Journal, 2019)
The steady state laminar mixed convection and radiation through inclined rectangular duct with an interior circular tube is investigated numerically for a thermally and hydrodynamicaly fully developed flow. The two heat transfer mechanisms of convection and radiation are treated independently and simultaneously. The governing equations which used are continuity, momentum and energy equations. These equations are normalized and solved using the Vorticity-Stream function and the Body Fitted Coordinates (B.F.C) methods. The finite difference approach with the Line Successive Over-Relaxation (LSOR) method is used to obtain all the computational results. The (B.F.C) method is used to generate the grid of the problem. A computer program (Fortran 90) is built to calculate the steady state Nusselt number (Nu) for Aspect Ratio AR (0.55-1) and Geometry Ratio GR (0.1-0.9). The fluid Prandtl number is 0.7, Rayleigh number Ra = 400, Reynolds number Re = 100, Optical Thickness (0 ≤ t ≤ 10), Conduction- Radiation parameter (0 ≤ N ≤ 100) and Inclination angle λ = 45. For the range of parameters considered, results show that radiation enhance heat transfer. It is also indicated in the results that heat transfer from the surface of the circle exceeds that of the rectangular duct. Generally, Nu is increased with increasing GR, t and N but it decreased with AR increase. When the radiation effect added to the heat transfer mechanism, the heat transfer rate increased. This effect increased with increasing in GR and decreasing with AR. The increasing in radiation properties lead to increase the radiation effect. Tecplot 7 program was used to plot the curves which cleared these relations and isotherms and streamlines which illustrate the behavior of air through the channel and its variation with other parameters. A correlation equation is concluded to describe the radiation effect. Comparison of the results with the previous work shows a good agreement.